Social support and its association with diet self-care in patients with diabetes - Alarcón-Mora, Cynthia (2017)
Type 2 diabetes mellitus is a major public health problem with many elements, such as self-care and social support, that could be interacting with its evolution. Nevertheless, there is no evidence of association between these two elements. Thus, this study aims to determine the relationship between medical, nutritional and physical activity self-care, perceived social support and duration of the disease. A cross-sectional Study was conducted on 126 people with diabetes with a mean age of 55 (±10.4) years old. The Summary of Diabetes Self-Care Activities Scale and the Medical Outcomes Study (MOS) Social Support Survey were applied. Social support, specifically the instrumental one, may generate negative effects by limiting self-care behavior of a person. Based on these findings, it is possible to conclude that social support does not always turn out to be beneficial for people: having more instrumental support generates dependency and no responsibility on the diet.  DOI: https://doi.org/10.24265/liberabit.2017.v23n1.08